2014
DOI: 10.7567/apex.7.065504
|View full text |Cite
|
Sign up to set email alerts
|

Improved passivation effect at the amorphous/crystalline silicon interface due to ultrathin SiOx layers pre-formed in chemical solutions

Abstract: To improve the passivation effect at a-Si:H/c-Si interface in heterojunction (HJ) solar cells, ultrathin SiOx layers with a thickness of approximately 2 nm were pre-formed on c-Si surfaces in chemical solutions. It was demonstrated that the SiOx layers pre-formed in hot de-ionized water and hydrochloric acid solutions improve effective carrier lifetime, and it is further enhanced through a post annealing process. When the thin SiOx layers were applied to HJ solar cells, increase in both Voc and Jsc was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…As reported in these papers [4][5][6][7][8], the photovoltaic characteristic of SIS solar cells has a strong dependence on the intermediate oxidation layer, which can act as passivity layer, tunneling function layer or inversion layer. Therefore, it is very important to determine the microstructure and property of this ultra-thin layer.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As reported in these papers [4][5][6][7][8], the photovoltaic characteristic of SIS solar cells has a strong dependence on the intermediate oxidation layer, which can act as passivity layer, tunneling function layer or inversion layer. Therefore, it is very important to determine the microstructure and property of this ultra-thin layer.…”
Section: Introductionmentioning
confidence: 97%
“…Transparent conducting indium tin oxide (ITO) materials are widely used in solar cells of various types because of its combined superior performances of optical transparency and excellent electrical conductivity. Thus, by depositing ITO films directly on Si wafers, a simple device structure of SIS heterojunction solar cells formed, possessing both comparatively highly efficient and lower cost, which aroused many attentions among researchers [2][3][4][5][6]. Giampiero de Cesare et al discussed the electrical properties of ITO/Crystalline-Silicon contact at different deposition temperatures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are passivated contacts in silicon solar cells [1,2], intermediate layers in metal-insulatorsemiconductor (MIS) solar cells [3], passivation of the amorphous/crystalline silicon (a-Si:H/c-Si) heterojunction [4][5][6], and barrier layer in silicon-based single and multi-junction quantum well solar cells [7,8]. Very recently, 25.1 % efficiency was achieved on a both sides-contacted Si solar cell featuring tunnel oxide passivated contacts [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that adding oxygen [30] or introducing a thin SiN x [26], or SiO x [31] interlayer can suppress epitaxial growth during a-Si:H(i) passivation. Moreover, the hydrogen trapping and oxygen incorporation suggests higher hydrogen concentration and different bonding configurations at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous researches have shown that the ultra-thin interlayer is not a detrimental factor to charge transport and solar cell efficiency. Bian et al [31] used chemically grown silicon oxide layer to improve short circuit current and open circuit voltage for HET cells; Feldmann et al [34] used ultra-thin SiO 2 as a passivation and carrier tunnelling layer. In our case, the interlayer is neither stoichiometric nor thick enough to affect charge transport.…”
Section: Resultsmentioning
confidence: 99%